The development and validation of an Islamic spiritual intelligence instrument for school leaders in Malaysia - Tajulashikin bin Jumahat (Kulliyyah of Education, International Islamic University Malaysia, 2018)
The purpose of this study was to develop a valid measure of Islamic spiritual intelligence for school leaders in Malaysia. Four theoretical dimensions were proposed, namely: a) Spiritual Awareness comprised of God Consciousness, Trust in God, and Repentance, b) Morality comprised of Patience, Truthfulness, and Forgiveness, c) Responsibility comprised of Justice and Integrity, d) Continuous Learning comprised of Religious Wisdom and Knowledge Sharing. Using the iterative technique of factor analytical procedure, the initial instrument was developed as a general scale, namely Islamic Spiritual Intelligence Measure (ISIM) in the pilot study to explore the dimensionality. Items were self-developed encompassing spirituality, religiosity, personality, and leadership aspects of the Islamic worldview. Face and content validity were conducted accordingly, ultimately settling 63 items for ISIM. A total of 380 usable data from Muslim postgraduate students in the pilot study were analyzed using exploratory factor analysis (EFA). The dimensionality of ISIM converged on nine factors with 32 viable items. Subsequently, some of the items in ISIM were adapted into a specific measure called Islamic Spiritual Intelligence for School Leaders Instrument (ISISLI). After further rigorous empirical content validation using Content Validity Ratio (CVR) procedure, 52 items qualified for the final study. There were 824 viable data of school leaders that attended courses at three branches of Institut Aminuddin Baki (IAB) were analyzed in the final study. The data were divided into two random data sets using SPSS 22. As an iterative undertaking, the first data set with 411 samples were subjected another series of EFA. The final exploration of ISISLI end up with 35 items and 60% total variance explained. The eight-factor measurement model of ISISLI was subjected to confirmatory factor analysis (CFA) procedure using AMOS 22 with 413 samples for the second data set. In this confirmatory mode, the measurement model of ISISLI demonstrated adequate fit and parameter estimates with slight model respecification, ending with 28 items. A bootstrapping method was then applied, and recommended that the data for the analysis were tenable. The construct validity evidence via convergent and discriminant validity were also adequate together with the reliability evidences. Two stages of invariance analysis across gender and age, namely factorial and matrix invariance disclosed the robustness of ISISLI. Interestingly, the eight-factor model of ISISLI also gained passable model fit for the second-order factor. Therefore, the preceding psychometric properties via factor analysis procedures have somewhat substantiated the practicality of ISISLI. All in all, the development of ISISLI has contributed to educational implications, research applicability in various fields, theoretical contributions as well as significantly contributing to the Islamization of Human Knowledge.